2018
DOI: 10.1074/mcp.ra118.000822
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Chemical Proteomic Strategy for Profiling Phosphoprotein Phosphatases from Yeast to Humans

Abstract: A "tug-of-war" between kinases and phosphatases establishes the phosphorylation states of proteins. While serine and threonine phosphorylation can be catalyzed by more than 400 protein kinases, the majority of serine and threonine dephosphorylation is carried out by seven phosphoprotein phosphatases (PPPs). The PPP family consists of protein phosphatases 1 (PP1), 2A (PP2A), 2B (PP2B), 4 (PP4), 5 (PP5), 6 (PP6), and 7 (PP7). The imbalance in numbers between serine- and threonine-directed kinases and phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…The western blot results showed that MC-LR entered HBx 4, HBx 32, and HBx cells in a time-dependent pattern ( Figure 2D). MC-LR is a well-known hepatotoxin that can greatly inhibit intracellular PP2A activity, which regulates HepG2 cell proliferation, differentiation, and invasion as well as the cell cycle (Sun et al, 2014;Lyons et al, 2018). Similarly, ctHBx could also affect the proliferation migration and invasion capabilities of HepG2 cells (Iavarone et al, 2003;Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The western blot results showed that MC-LR entered HBx 4, HBx 32, and HBx cells in a time-dependent pattern ( Figure 2D). MC-LR is a well-known hepatotoxin that can greatly inhibit intracellular PP2A activity, which regulates HepG2 cell proliferation, differentiation, and invasion as well as the cell cycle (Sun et al, 2014;Lyons et al, 2018). Similarly, ctHBx could also affect the proliferation migration and invasion capabilities of HepG2 cells (Iavarone et al, 2003;Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Vital hallmarks change in the process of EMT, such as downregulation of epithelial markers (E-cadherin) and the upregulation of mesenchymal marker (Vimentin) [6]. The PPP family has seven members, including Protein Phosphatases1 (PP1), 2A (PP2A), and 2B (PP2B) [7]. These members are involved in EMT through regulating the expression of EMT markers and modulating a broad range of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…1B-C, Table S1). In a complementary approach, we incubated lysates from untreated or iHAP1/DT-061 treated HEK-293T cells with microcystin coupled to beads and analysed by mass spectrometry the composition of endogenous PPP components which were pulled down by microcystin [15] (Fig. 1D, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…PIB pull-downs were analysed on a Q-Exactive Plus quadrupole Orbitrap mass spectrometer (ThermoScientific) equipped with an Easy-nLC 1000 (ThermoScientific) and nanospray source (ThermoScientific) as previously described [15]. Raw data were searched using COMET (release version 2014.01) in high resolution mode [46] against a target-decoy (reversed) [47] version of the human proteome sequence database (UniProt; downloaded 2/2020) with a precursor mass tolerance of +/- 1 Da and a fragment ion mass tolerance of 0.02 Da, and requiring fully tryptic peptides (K, R; not preceding P) with up to three mis-cleavages.…”
Section: Methodsmentioning
confidence: 99%